The Importance of General Self-Efficacy for the Quality of Life of Adolescents with Diabetes or Juvenile Rheumatoid Arthritis Over Time: A Longitudinal Study among Adolescents and Parents - Cramm, Jane M. (Frontiers Media S.A., 2013)
Purpose: To (i) investigate the influence of general self-efficacy on quality of life outcomes over time among adolescents with type I diabetes or juvenile rheumatoid arthritis (JRA), (ii) investigate parents’ perceptions of general self-efficacy and quality of life of adolescents with diabetes or JRA over time, and (iii) identify possible differences in the evaluations of adolescents and parents. Methods: This study included adolescents aged 12–25 years with type I diabetes or JRA and their parents. At T1, 171/573 (30% response rate) adolescents with diabetes or JRA and 229/563 (41% response rate) parents completed the questionnaire. At T2, 230/551 (42% response rate) adolescents and 220/559 (39% response rate) parents still participating in the study completed the questionnaire. A total of 112 adolescents and 143 parents filled in the questionnaires at both T1 and T2. Results: Adolescents perceived significant improvement in their general self-efficacy and reduced quality of life over time, whereas parents’ perceptions did not change. According to adolescents and parents, physical functioning was better among adolescents with diabetes than among those with JRA. Regression analyses of adolescents’ data showed that general self-efficacy at T1 (β = 0.13; p ≤ 0.10) and changes in general self-efficacy (β = 0.22; p ≤ 0.01) predicted quality of life at T2. Parents’ responses revealed that adolescents’ general self-efficacy at T1 (β = 0.16; p ≤ 0.05) and changes in adolescents’ general self-efficacy (β = 0.18; p ≤ 0.05) predicted adolescents’ quality of life at T2. Conclusion: General self-efficacy and changes therein positively affected quality of life in adolescents with diabetes or JRA over time, as perceived by adolescents and parents. These findings emphasize the need for the implementation of interventions aiming to improve general self-efficacy in these populations.